Frevo: The State of the Art in Music - Santos, Marília (Global Journal of Cultural Studies, 2023)
Frevo is a Brazilian cultural expression composed of music and dance. Its musical genre is popular, but part of its musical structure is based on classical music theory. In recent years, research on frevo music has been growing. This is likely related to the recognition of frevo as Intangible Cultural Heritage of Humanity. In this literature review, I present the current state of the art of frevo music. Research on frevo music is primarily focused on the field of Ethnomusicology and technical aspects, such as technical and interpretive analysis.